Зміни вмісту біологічно активних сполук бебі-шпинату під час зберігання - Прісс, Олеся Петрівна; Яковер, Олександр Ігорович; Колісниченко, Тетяна Олександрівна; Булгаков, Павло Олександрович; Priss, Оlesia; Yakover, Oleksandr; Kolisnychenko, Tetiana; Bulgakov, Pavlo (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Досліджено зміни вмісту біологічно активних сполук бебі-шпинату (Spinacia oleracea L.) під час зберігання в живильному середовищі на основі хітозану та рутину порівняно з контролем. Зберігали сорти шпинату Траверс, Такома, Трейлбос за температури 7 ± 0,5 °C та відносної вологості повітря вологості 95 ± 3 %. Оцінювали сухі речовини, аскорбінову кислоту, суму хлорофілів (a + b) та фенольних сполук. Установлено, що застосування живильного середовища істотно сповільнює деградацію компонентів: через 6 діб втрати фенолів скоротилися щонайменше вдвічі, хлорофілів у 2–6 разів менші, а збереження вітаміну С було на 20–30 % вищим. Після 12 діб зберігання збережено 65–80 % початкового рівня хлорофілів та понад 80 % аскорбінової кислоти (залежно від сорту). Запропонований підхід подовжує період свіжості бебі-шпинату та підтримує його біохімічний склад. /// EN: The study investigates the dynamics of biologically active compounds in baby spinach (Spinacia oleracea L.) during postharvest storage in a nutrient medium based on natural chitosan and the flavonoid rutin, compared with conventional storage conditions. The experiment aimed to assess the effect of the chitosan–rutin medium on the preservation of dry matter, ascorbic acid, total chlorophylls (a + b), and phenolic compounds in spinach leaves of three cultivars–Travers, Tacoma, and Trailboss–during refrigerated storage at 7 ± 0.5 °C and 95 ± 3 % relative humidity. The results demonstrated that all cultivars exhibited a gradual decline in biochemical indicators during storage; however, samples stored in the chitosan–rutin (X + P) medium maintained significantly higher levels of active substances compared to the control. After six days, losses of phenolic compounds in the treated samples were reduced by two to three times (12–15 % vs. 25–44 % in control), and the degradation of chlorophylls decreased 2–6 fold, which effectively delayed leaf yellowing. The retention of ascorbic acid was also substantially improved: vitamin C content remained 20–30 % higher than in the control. After twelve days of storage, spinach maintained 65–80 % of its initial chlorophyll level and more than 80 % of ascorbic acid, depending on the cultivar. The obtained data confirm that chitosan and rutin act synergistically: chitosan forms a semi-permeable film that reduces transpiration and oxygen permeability, while rutin exhibits pronounced antioxidant properties, neutralizing reactive oxygen species and stabilizing cell membranes. The combination provides both barrier and antioxidant protection, slowing oxidative degradation of pigments and phenolics and extending the shelf life of baby spinach without synthetic preservatives. The proposed eco-friendly approach is consistent with sustainable food preservation strategies, reducing postharvest losses and maintaining nutritional and sensory quality. The findings support the feasibility of using biodegradable chitosan-flavonoid coatings as an alternative to conventional packaging for leafy vegetables.
Changes in the content of biologically active compounds in baby spinach during storage
Keywords: бебі-шпинат; хітозан; рутин; фенольні сполуки; хлорофіли; аскорбінова кислота; зберігання; біополімери; антиоксиданти; baby spinach; chitosan; rutin; phenolic compounds; chlorophylls; ascorbic acid; postharvest storage; biopolymers; antioxidants